Two Morphological Awareness Components Have Different Roles in Chinese Word Reading Development for Primary Schoolers - Liu, Hailun; Wang, Jing; Wang, Lei; Zhang, Wenjun; Deng, Ciping (Frontiers in Psychology, 2022)
Morphological awareness is multi-factorial by nature and consists of general morphological knowledge and morphological meaning analysis; the first refers to the recognition and manipulation of morphological structures and the second refers to the inference of word semantics by utilizing morphological knowledge. Contrasting the roles of two morphological awareness components in word reading could help resolve the controversy about whether morphological awareness could independently contribute to Chinese word reading. Thus, the study explored how morphological awareness components contributed to word reading development in Chinese context. A group of 299 Chinese children in grades 3 and 4 were recruited, and tested twice with the interval of half a year, by a series of tasks on morphological awareness components, word reading, and some control variables. Results showed that, after controlling for vocabulary and other linguistic variables, morphological meaning analysis could independently predict word reading, whereas general morphological knowledge could only indirectly predict word reading, a process mediated by morphological meaning analysis. This study showed independent contribution of morphological awareness to Chinese word reading development. By clarifying the ways of how different morphological awareness components support children’s word reading development, the findings enhance our understanding about the potential mechanism underlying the relation between morphological awareness and Chinese word reading.